Answer: b
Step-by-step explanation:
Answer: 15
Step-by-step explanation:
x = one point shots
y = two point shots
1) Setup your equations.
x + y = 52
x + 2y = 89
2) Isolate a variable.
x = 52-y
3) Plug in.
(52-y) + 2y = 89
52 +y =89
y=37
4) Solve for x.
x = 52 -37
x=15
5) Check your answer.
15 + 2(37) = 89
15+74=89
89=89
37+15 = 52
52=52
x = one point shots
y = two point shots
1) Setup your equations.
x + y = 52
x + 2y = 89
2) Isolate a variable.
x = 52-y
3) Plug in.
(52-y) + 2y = 89
52 +y =89
y=37
4) Solve for x.
x = 52 -37
x=15
5) Check your answer.
15 + 2(37) = 89
15+74=89
89=89
37+15 = 52
52=52
Answer:
the answer is 8 by one of this question.
He needs $78.95 to buy 5 of each
Answer:
Step-by-step explanation:
<u>Given </u><u>:</u><u>-</u><u> </u>
- A quadratic equation is given to us.
- The equation is 2x² + 7x +6=0
And we need to find out the roots of the given equation. We can use the middle term splitting method to find out the roots as ,
<u>Given </u><u>equation</u><u> </u><u>:</u><u>-</u>
Step 1: <u>Find</u><u> out</u><u> the</u><u> </u><u>factors</u><u> </u><u>of </u><u>1</u><u>2</u><u> </u><u>:</u><u>-</u><u> </u>
We will choose the two factors such that their sum equals to the coefficient of x i.e. 7 .The factors are , 1×12 , 2×6 , 3×4 .
- And 3 + 4 = 7. So we will break the middle term into 3x and 4x .
Step 2 :<u> Breaking</u><u> the</u><u> </u><u>middle</u><u> term</u><u> </u><u>:</u><u>-</u><u> </u>
Step 3: <u>Take </u><u>out </u><u>common</u><u> </u><u>from </u><u>terms </u><u>:</u><u>-</u>
Step 4 : <u>Equate </u><u>them </u><u>with </u><u>0</u><u> </u><u>:</u><u>-</u><u> </u>
<u>Hence </u><u>the</u><u> </u><u>correct</u><u> </u><u>options </u><u>are </u><u>C </u><u>and </u><u>D </u><u>.</u>